Device‐to‐device communications using EMTR technique. Issue 3 (1st May 2018) - Rajabi, Siavash; Ghorashi, Seyed Ali; Shah‐Mansouri, Vahid; Karami, Hamidreza
Abstract : Device‐to‐device (D2D) communication is a promising 5G technology, which helps to increase spectrum efficiency and sum‐rate, as well as to decrease experienced latency. The main challenges of D2D communication are power consumption of paired devices, channel estimation between device pairs, and interference management between devices that use the same time and frequency resources. The electromagnetic time reversal (EMTR) technique is used in D2D communications to focus the signal power in both time and space domains for power efficiency of end users, to simplify the structure of transceivers, to help channel estimation in a low complexity way, and to nullify the effect of interference. First, in the time domain, the effect of using EMTR technique is investigated and its performance is compared with a similar non‐EMTR system. Then, EMTR technique is used in an OFDM‐based system and its advantages in the context of signal to interference plus noise ratio (SINR) and sum‐rate are presented analytically and through computer simulations. Simulation results show a significant gain in SINR, sum‐rate and received signal power for the proposed EMTR‐based D2D system.